2006
DOI: 10.1002/uog.2797
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings of placental lacunae and the prediction of adherent placenta in women with placenta previa totalis and prior Cesarean section

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 18 publications
4
91
1
11
Order By: Relevance
“…The use of ultrasound in assessing the extent of myometrial involvement in partial placenta accreta Placenta accreta has been reported in up to 0.9% of pregnancies and remains a cause of maternal mortality 1 . Placenta accreta is usually subdivided into 'total' (involving the whole placenta), 'partial' (involving one or more lobe)…”
mentioning
confidence: 99%
“…The use of ultrasound in assessing the extent of myometrial involvement in partial placenta accreta Placenta accreta has been reported in up to 0.9% of pregnancies and remains a cause of maternal mortality 1 . Placenta accreta is usually subdivided into 'total' (involving the whole placenta), 'partial' (involving one or more lobe)…”
mentioning
confidence: 99%
“…A study by "Tseng et al, (2006) [32]" has previously noted increased VEGFR expression in a cohort of patients with placenta accreta. The sonographic appearance of intraplacental sonolucent spaces (lakes or lacunae) is a frequent finding in cases of suspected placenta accreta "as solved by (Yang et al, 2006) [33]". The pathophysiology behind the occurrence of placental lacunae is unknown, but their presence suggests an aberrant vascular remodeling pattern "as solved by (Comstock et al, 2004) [34]".…”
Section: Discussionmentioning
confidence: 99%
“…The sonographic appearance of intraplacental sonolucent spaces (lakes or lacunae) is a frequent finding in cases of suspected placenta accreta "as solved by (Yang et al, 2006) [33]". The pathophysiology behind the occurrence of placental lacunae is unknown, but their presence suggests an aberrant vascular remodeling pattern "as solved by (Comstock et al, 2004) [34]". It was observed that there was prominent VEGFR staining in the vascular lacunae of the patients with previa accreta Fig: (7e, 8d, 13c, 17d).…”
Section: Discussionmentioning
confidence: 99%
“…Since, intraplacental lacunae are associated with adherent placenta, they may be used to predict obstetric complications. 28 Reduced anterior myometrial thickness (less than 1 mm) as measured between the echogenic serosa and the retroplacental vessels is also reported to be as predictive as placental lacunae for placenta accreta (Figs 15 and 16). 23 Absence of the hypoechoic zone is thought to represent a defect in decidua basalis and adjacent myometrium and has also been seen in normal pregnancies.…”
Section: Case 5: Placenta Accretamentioning
confidence: 97%